Music as an alternative therapy method in dentistry - Jovanović-Medojević Milica; Nešković Jelena; Medojević Aleksandar (Serbian Medical Society - Dental Section, Belgrade, 2016)
Dental fear represents a significant social concern. Therefore, an individual approach to each patient and timely recognition and elimination of dental stress are necessary in order to provide adequate and successful treatment. The aim of this paper was to present possible application of music therapy in dentistry and its role in reducing dental fear. Music has shown great prospective as an alternative therapy method in various fields of medicine. Music therapy is painless and noninvasive anxiolytic method that reduces dental anxiety as it provides relaxation and distraction. Music in dental office creates positive atmosphere among patients and their company as well as dental staff.